Screening and Identification of Potato StSPS1, a Potential Crucial Gene Regulating Seed Potato Vigor - Chengcheng Cai; Shifeng Liu; Jie Liu; He Wen; Luopin Li; Qiang Wang; Liqin Li; Xiyao Wang (Horticulturae, 2023)
Sucrose phosphate synthase (SPS), a crucial rate-limiting enzyme that catalyzes the synthesis of precursors of sucrose, plays an indispensable role in the regulation of seed potato vigor. Nonetheless, the genes that encode SPS in potato have not undergone complete analysis, and the primary genes responsible for the regulation of seed potato vigor have not been screened and identified. In this study, four StSPS family members were identified by comparing the potato genome database with homologous proteins. Using bioinformatics, the physicochemical properties, subcellular localization, sequence structure, conserved motifs, and phylogenetics of StSPS were analyzed. The expression levels of StSPS in different potato tissues, from dormancy to sprouting in the seed potato tubers, were measured via qRT-PCR. The expression data from the potato genome database and previous transcriptome and proteome studies of dormancy to sprouting were also compared. After combining the analysis of SPS enzyme activity in diverse tuber tissues and the correlation analysis between multiple varieties with different dormancy periods and the expression of StSPS1, the primary gene StSPS1 that might regulate seed potato vigor was identified. This study set a theoretical and experimental groundwork for further verification and clarification of the regulatory function of StSPS1 in alterations in seed potato vigor.